Structured fluids as colorful paintable radiative coolers - Kim, Hyeon Ho; Kwak, Soyul; Lee, Jaewon; Im, Eunji; Raman, Aaswath P.; Lee, Seungwoo (Cell Press, 2024)
Radiative cooling has emerged as a promising materials-driven approach to enabling passive cooling for terrestrial structures. The prevalent wavelength-selective, solar absorption-driven colorization strategies have hindered cooling performances, especially during the daytime. In this study, we present a structured fluids platform that can simultaneously achieve extremely low absorption across the solar spectrum (z3%) z 3%) and preservation of omnidirectional, full-color characteristics. In addition, it serves as an ideal broadband emitter in the infrared (IR) range, with an emissivity of up to 0.94. This enables sub-ambient ( 2 K) daytime radiative cooling with a power of 40 W/m2 2 on a reflective substrate. In addition, on an absorptive substrate, the structured fluids effectively cool the substrate by up to 9.5 K with a power of 120 W/m2. 2 . Furthermore, the exotic fluidity of structured fluids facilitates compatibility with scalable painting and molding, offering versatile and efficient solutions for sustainable energy-saving cooling applications beyond conventional radiative methods.